2024 UK General Election: conservative defeat and the fragmentation of British politics - Benites, Alexander; Unsworth, Charlie (Revista Elecciones, 2025)
The 2024 United Kingdom (UK) General Election has been characterised as the most fragmented and disproportionate in the country’s long-standing democratic history. Regarded as a classic example of a two-party system, the UK’s political landscape now exhibits growing volatility, with class-based loyalties eroding and new political actors emerging. This paper offers initial insights into this dynamic moment by examining the key campaign themes and outcomes of the 2024 General Election. Taking the magnitude of the Conservative Party’s defeat as one of the defining features of the election—and an important example of increasing party-system fragmentation—multivariate statistical models are employed to explore initial associations between the loss of party support and political as well as sociodemographic indicators at the constituency level. The findings highlight two main themes: the intensification of political volatility and the enduring impact of Brexit, which continues to shape political competition through deep-seated demographic and value-based divisions. For the Spanish version click here